DAMPAK KEHADIRAN MINIMARKET PADA KONDISI SOSIAL EKONOMI PEDAGANG TRADISIONAL DI KOTA TIDORE PROVINSI MALUKU UTARA - Ridwan Umar; Hamdi Gugule; Nismawati Nismawati (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2021)
Traditional traders are traders who carry out the trading process in traditional markets and the buildings usually consist of stalls and open grounds opened by sellers or a market manager and with an uncertain price system. The method approach used in this research is a qualitative method which aims to provide a systematic, factual and accurate description. Based on research on how the impact of the presence of minimarts on the socio-economic conditions of traditional traders in the city of Tidore, North Maluku Province, it turns out that the presence of minimarkets has an impact on traditional traders. Moreover, the negative impacts such as decreasing income of traditional traders, loss of livelihood, children dropping out of school and increasing poverty levels, while the positive impacts make it easier for traditional traders to get merchandise. To anticipate the negative impact of the presence of the minimarket, some traders also make efforts by doing side jobs. This also deserves the attention of the local government to overcome problems related to the impact of minimarkets that are felt by traditional traders so that it does not have an impact on the socio-economic life of the community.